PERBEDAAN KUANTITAS SEKRESI AIR MATA MAHASISWA DAN MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA MENGGUNAKAN UJI SCHIRMER 1 - ZEID ALFAN MADHY; ZALDI Z (LP2MTBM MAKARIOZ, 2020)
Vision is one of the most important part that we have got. The tear plays fundamental roles in keeping the clarity of thecornea, in providing a clear vision for the defense of mechanism of the eye. The tears spread across the eye and has threelayersnamely lipid layer, the aqueous layer and the mucous layer. Lipid layer (secrete lipid) as a barrier and prevent thefrequent hydrophobic tears. The composition of the tears that are not effective can disrupt homeostasis and stability of ocularsurface. Although the causes of dry eye syndrome are multifactorial, largely due to a deficiency of one or more componentsof a tear, causing ocular surface abnormality and the onset of the diseases. To determine the differences in tear secretions inUMSU Faculty of Medicine students using the Schirmer Test 1. Observational analytic with cross sectional design.The results of this study using the Shapiro-Wilk test obtained a value of P> 0.05 so that the data were normally distributed.Data analysis using paired t test. The results of the paired test t test obtained a significant value of 0,000 (P <0.05) with adifference of -4,706. Because the P value <0.05 and the IK did not cross zero, there was a statistically significant differencein tear secretion with a significant Schirmer 1 test for students and FK UMSU students. There is a difference in quantity oftear secretion and sorority students faculty of medicine Muhammadiyah University of North Sumatra using Schirmer Test 1.